1997
DOI: 10.1016/s0029-7844(97)00254-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplementation and the risk of preeclampsia in ecuadorian pregnant teenagers

Abstract: These results suggest that calcium supplementation during pregnancy in populations with low calcium intake is a safe, effective, and inexpensive preventive measure that significantly reduces the risk of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 10 publications
1
74
0
2
Order By: Relevance
“…These observations were the initial support of our earlier clinical trials carried out to determine the role of calcium supplementation in Andean pregnant women (7)(8)(9)(10), a population with a low calcium intake (11).…”
Section: Calcium Supplementation and Preeclampsia: From Epidemiologicsupporting
confidence: 55%
“…These observations were the initial support of our earlier clinical trials carried out to determine the role of calcium supplementation in Andean pregnant women (7)(8)(9)(10), a population with a low calcium intake (11).…”
Section: Calcium Supplementation and Preeclampsia: From Epidemiologicsupporting
confidence: 55%
“…Between 1984 and 1995 we conducted three randomized, double-blind, placebo-controlled clinical trials including pregnant nulliparous women, younger than 25 years, who had their first prenatal visit before 24 weeks of gestation, normotensive, and were residents of Quito (2800 m above sea level) [13][14][15]. These studies showed a beneficial effect of calcium supplementation in preventing PIH and PE (Table 1).…”
Section: Preventing Pe: Effects Of Nutritional Interventionmentioning
confidence: 99%
“…Data reported as means AE standard deviation. a,b,c Data from references [13], [14] and [15], respectively. Ã P < 0.001 and ÃÃ P < 0.01.…”
Section: Antioxidantsmentioning
confidence: 99%
“…In populations where dietary calcium intake is low, randomized, controlled trials have demonstrated that calcium supplementation during pregnancy significantly decreases the risk of HDP and HDP-associated adverse outcomes (2)(3)(4)(5)(6). Furthermore, prenatal calcium supplementation was identified as the only intervention to prevent HDP that may be feasibly delivered at the community level (7).…”
Section: Introductionmentioning
confidence: 99%